The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.2147/ott.s99959
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels and diagnostic utility of VEGF, MMP-9, and TIMP-1 in the diagnosis of patients with breast cancer

Abstract: Vascular endothelial growth factor (VEGF), matrix metalloproteinase-9, and tissue inhibitor of metalloproteinase-1 may play a role in the pathogenesis of cancer disease. We investigated their levels and utility in comparison to cancer antigen (CA) 15-3 in patients with breast cancer (BC) and in relation to the control groups. The study included 100 women with BC, 50 patients with benign breast tumor, and 50 healthy women. The plasma levels of the tested parameters were determined using enzyme-linked immunosorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 56 publications
5
35
1
2
Order By: Relevance
“…Unfortunately, we could not compare our data regarding MMP-7 and tissue inhibitor of metalloproteinase −1 with other publications. A positive correlation between TIMP-1 and CA15–3 concentrations in a group including 100 breast cancer patients (stages I-IV) ( R  = 0.28) has also been previously revealed [39]. Some authors have demonstrated significant positive correlations between CA125 and HE4 levels in patients with ovarian malignancies ( R  = 0.54) [44, 45].…”
Section: Discussionmentioning
confidence: 69%
“…Unfortunately, we could not compare our data regarding MMP-7 and tissue inhibitor of metalloproteinase −1 with other publications. A positive correlation between TIMP-1 and CA15–3 concentrations in a group including 100 breast cancer patients (stages I-IV) ( R  = 0.28) has also been previously revealed [39]. Some authors have demonstrated significant positive correlations between CA125 and HE4 levels in patients with ovarian malignancies ( R  = 0.54) [44, 45].…”
Section: Discussionmentioning
confidence: 69%
“…) is in the range of other optical label-free platforms making use of surface waves, it is still larger than previously reported plasma VEGF concentrations in healthy humans and cancer patients, ranging from a few tens to a few hundreds of pg/ml (Iinuma, 2010;Jelkmann, 2001;Ławicki et al, 2016). We calibrated the operation in the fluorescence detection mode by setting the minimum concentration measured in label-free mode as the largest for fluorescence.…”
Section: Despite the Lodlf (And γmentioning
confidence: 99%
“…In addition, AUC increased to 0.938 (0.903–0.973). Compared with other studies of combined diagnostic indicators, our results exhibit a clinical advantage 5,50…”
Section: Discussionmentioning
confidence: 44%
“…Carbohydrate antigen 153 is a tumor marker for breast cancer, although its diagnostic sensitivity and specificity are limited 14,15. Recently, new indicators for diagnosing breast cancer have been studied, including free DNA in the plasma, microRNA, long-chain non-coding RNA, and vascular endothelial growth factor 5,1621…”
Section: Introductionmentioning
confidence: 99%